MATHEMATICAL APPROACH ON HOUSEHOLD WASTE CAUSING ENVIRONMENTAL POLLUTANTS DUE TO LANDFILL AND TREATMENTS - Shah, Nita; Satia, Moksha; Thakkar, Foram (International Journal of Engineering Technologies and Management Research, 2018)
Household solid waste is the solid waste mixture of garbage and rubbish which comes during the use of various products in daily life. It also called as domestic waste or residential waste. It may fall into two categories either hazardous or non-hazardous which are stored and forsaken directly to the landfills. This is how household solid waste plays vital role in spreading environmental pollutants. For reduction of the pollution, treatment plant is constructed for hazardous solid waste and compost plant is organized for non-hazardous solid waste. In this paper, we have developed a system of non-linear differential equations to analyse the household solid waste storage. In order of preventive measures, five various controls are given to the different compartments. The basic reproduction number and the stability are derived to check the endurance of the model. The numerical simulation is also done using validated data.